2004
DOI: 10.1155/2004/383461
|View full text |Cite
|
Sign up to set email alerts
|

The Costs and Consequences of Methicillin‐Resistant Staphylococcus aureus Infection Treatments in Canada

Abstract: BACKGROUND: A multinational randomized controlled trial has shown a trend toward early discharge of patients taking oral linezolid versus intravenous vancomycin (IV) in the treatment of methicillin-resistantStaphylococcus aureus(MRSA) infections. Infection treatments resulting in shorter hospitalization durations are associated with cost savings from the hospital perspective.OBJECTIVE: To determine whether similar economic advantages are associated with oral linezolid, the costs and consequences of linezolid u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Controlling MRSA infection can be expensive and labour intensive, and can cause considerable disruption of clinical services (42). Several Canadian studies have investigated health care resource utilization and the direct medical costs associated with MRSA infection (22,(24)(25)(26)(27). Substantial variation was observed among studies in methodologies used and depth of analyses, as well as in their measures of health care utilization, resources included in estimates, cost per component and total cost per patient ( The cost of antimicrobial therapy was included in only two studies, and varied between $325 and $574 ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Controlling MRSA infection can be expensive and labour intensive, and can cause considerable disruption of clinical services (42). Several Canadian studies have investigated health care resource utilization and the direct medical costs associated with MRSA infection (22,(24)(25)(26)(27). Substantial variation was observed among studies in methodologies used and depth of analyses, as well as in their measures of health care utilization, resources included in estimates, cost per component and total cost per patient ( The cost of antimicrobial therapy was included in only two studies, and varied between $325 and $574 ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The present review indicated that Canadian patients infected with MRSA required prolonged hospitalization (average 26 days, range 14 to 36 days), comprising, on average, 81% of the total cost. Several studies have indicated that appropriate switching of MRSA patients from intravenous to oral treatment could reduce the length of hospital stay and cost per infected patient (26,41,45), suggesting that oral therapy may be one strategy to reduce the economic impact of MRSA. Cost estimates in the literature have varied from $7,222 to $14,630 per infected MRSA patient in Canada.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, analyses of outcomes in a multinational trial of vancomycin versus linezolid in patients with cSSTIs due to MRSA showed that the length-of-stay and early-discharge advantages for linezolid differed according to country, due to regional variation in clinical practice (16), and no study has compared the total costs of cSSSI treatment with linezolid versus vancomycin in Canada based on established clinical practice. The only previous Canadian cost simulation suggesting linezolid could be cost saving relative to vancomycin for patients with SSTIs was based on extrapolations from chart review data in the period before the availability of linezolid in Canada (17). The objective of the present study was to evaluate the potential cost impact in Quebec of using IV and PO linezolid instead of IV vancomycin to treat cases of cSSSI caused by MRSA that are severe enough to require hospitalization, based on current treatment patterns in Quebec.…”
Section: Cost Comparison Of Linezolid Versus Vancomycin For Treatmentmentioning
confidence: 99%
“…Rosner et al 87 reviewed the charts of all eighty-nine patients with methicillin-resistant Staphylococcus aureus infections admitted to a teaching hospital and treated with either intravenous administration of vancomycin or linezolid. The total hospital and nonhospital costs were higher in the vancomycin-treated group (Can$8444 per patient) compared with the linezolid-treated group ($7693 per patient), which had a one-day shorter length of stay with the patients discharged on oral linezolid.…”
Section: Non-necrotizing Soft-tissue Infections: the Additional Finanmentioning
confidence: 99%